DEVELOPING SCORING RUBRIC: DO THE STUDENTS NEED IT? - Aninda nidhomil Hima; Teguh Hadi Saputro (IAIN Syekh Nurjati Cirebon, 2017)
Abstract: For many reasons, the use of scoring rubrics has acquired more attention. However, the number of studies investigating the perception and the writing performance as well as the relationship between those two variables in the use of rubric is limited. Therefore, by involving 27 students in Writing -class of an English Language Education Department at a particular university in Indonesia, the present study aimed to explore the students’ perceptions through surveys and their writing performance in the three different situations in which they had no scoring rubric, generate their own scoring rubric and had teacher-made scoring rubric prior to the writing tasks. Also, the study was intended to explore how the students perceived the three situations related to their writing performance. After analyzing the data, it was found that the most helpful situation for the students was the second situation. It also helped the students to achieve the higher score compared to the other two situations. However, there was a contradictory finding in which the students’ perception and their performance were negatively correlated. Keywords: developing scoring rubrics, writing performance, students’ perception